2022
DOI: 10.3390/ijerph19159750
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Remote Sensing Ecological Index Based on Soil and Water Conservation on the Effectiveness of Management of Abandoned Mine Landscaping Transformation

Abstract: Abandoned mines are typical areas of soil erosion. Landscape transformation of abandoned mines is an important means to balance the dual objectives of regional ecological restoration and industrial heritage protection, but the secondary development and construction process of mining relics require long-term monitoring with objective scientific indicators and effective assessment of their management effectiveness. This paper takes Tongluo Mountain Mining Park in Chongqing as an example and uses a remote sensing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The mean value of NDVI was 0.6069, and the mean value of WET was 0.4603. It can be concluded that the eigenvalue of greenness was greater than that of wetness [79]. NDVI had a maximum value of 0.8025 in 2005, while WET had a maximum value of 0.5272 in 2010.…”
Section: Rsei Model Resultsmentioning
confidence: 93%
“…The mean value of NDVI was 0.6069, and the mean value of WET was 0.4603. It can be concluded that the eigenvalue of greenness was greater than that of wetness [79]. NDVI had a maximum value of 0.8025 in 2005, while WET had a maximum value of 0.5272 in 2010.…”
Section: Rsei Model Resultsmentioning
confidence: 93%
“…WET showed the lowest contribution, indicating a less significant effect on ecological quality. Additionally, the sum of the eigenvalues for LST and NDSI surpassed the total value of the eigenvalues of NDVI and WET, indicating weaker ecological enhancement from vegetation and humidity relative to the adverse influence of dryness and heat [48]. The WET indicator had the highest average values in 1990 and 2021, whereas LST consistently had the lowest average value.…”
Section: Rsei Quality In Chiba Prefecturementioning
confidence: 95%
“…The ecological index based on remote sensing is developed to quantify ecological quality by integrating four ecological factors: SAVI, NDBI, NDSI, and NDMI. These factors were selected based on a review of existing research (Jiang et al 2020;Lian et al 2022). Firstly, the dynamics of land use change, particularly in urban settings, alter the conditions and procedures of ecological study.…”
Section: Development Of Ecological Index Remote Sensing Datamentioning
confidence: 99%